Endowing single-crystal polymers with circularly polarized luminescence - Zhong-Qiu Li; Li Meng; Zili Chen; Yu-Wu Zhong (Nature Communications)
Abstract The preparation of single-crystal polymers with circularly polarized luminesce (CPL) remains a challenging task in chemistry and materials science. Herein, we present the single-crystal-to-single-crystal topochemical photopolymerization of a chiral organic salt to achieve this goal. The in-situ reaction of 1,4-bis((E)-2-(pyridin-4-yl)vinyl)benzene (1) with chiral (+)- or (−)-camphorsulfonic acid (CSA) gives the monomer crystal 1[( + )/( − )-CSA]2 showing yellow CPL with a high luminescent dissymmetry factor |g lum| of 0.035 and emission quantum yield Φ of 49.7%. Upon photo-induced topochemical [2 + 2] polymerization, single-crystal polyionic polymers of poly-1[( + )/( − )-CSA]2 are obtained. The single-crystal-to-single-crystal (SCSC) photopolymerization is revealed by in situ powder X-ray diffraction, single-crystal X-ray, optical microscopy, infrared, circular dichroism, and CPL spectroscopic analyzes. Interestingly, the photopolymer crystals show blue and handedness-inverted CPL with |g lum| of 0.011 (Φ = 14.2%), with respect to the yellow CPL of the monomer crystal. Furthermore, patterned circularly-polarized photonic heterojunctions with alternate blue and yellow CPL sub-blocks are prepared by a mask-assisted photopolymerization method. Our findings provide a vision for fabricating high-performance CPL-active crystalline polymer materials, paving the way for the further development of photo-response chiral systems.